Pengaruh Profitabilitas, Leverage, Sales Growth, dan Umur Perusahaan Terhadap Tax Avoidance - Sangian, Angel Martasya; Lestari, Indah Rahayu (PT Hakhara Akademia Indonesia, 2025)
This research aims to determine the effect of profitability, leverage, sales growth, and firm age on tax avoidance. The population in this study consists of property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in the financial statements for the 2020–2024 period, totaling 85 companies. The sampling technique used in this study is purposive sampling, which resulted in 45 companies as the sample. The data analysis technique used is multiple linear regression analysis with the assistance of SPSS version 22.0 software. The results of this study indicate that leverage has a positive and significant effect on tax avoidance. Meanwhile, profitability, sales growth, and firm age do not have a significant effect on tax avoidance.